100 exercises to get you into drama school : improve your acting and audition skills - Howl, Jona. (London : Methuen Drama, 2008)
A full-color, illustrated guide to improving acting skills through 100 different acting projects that focus on voice, movement, text, and character.
"A Quarto book"--T.p. verso.
Includes bibliographical references and index.
Adult
Keywords: Acting; Movement (Acting).